PARENTING QURANI SEBAGAI SOLUSI FATHERLESS STUDI KONTEKSTUAL ATAS KEHIDUPAN NABI MUHAMMAD - Nur Anisa Septiani; Hayani Hayani (Al Kareem Jurnal Ilmu Al Qur'an dan Tafsir, 2025)
The fatherless phenomenon is a major challenge in today's parenting crisis due to its enormous impact on children's development. This article examines Qur'anic parenting as a solution to the fatherless phenomenon through a contextual study of the life of the Prophet Muhammad SAW. The study used a qualitative research approach with a thematic interpretation method and content analysis. The results of this study demonstrate that Qur'anic parenting can minimize the phenomenon of fatherlessness in today's world. Qur'anic parenting can minimize the phenomenon of fatherlessness nowadays. Based on the study of the life of the Prophet Muhammad, some things that can be applied in the current era include creating a good environment and fulfilling children's emotional need for a father figure who can provide values such as godliness, exemplarity, and democratic communication. Thus, Quranic parenting is an alternative solution to the crisis of fatherhood in the modern era.